The impact of willingness to pay, environmental awareness, consumer behavior, consumer attitudes toward purchase decisions on sustainable packaging in Indonesia - Tanzares, Jordan; Rahmiati, Filda; Jokhu, Jean Richard; Mangkurat, R. Stevanus Bayu (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Packaging is considered a vital component of the marketing mix. Sustainable Packaging is packaging that is very important to use in Indonesia because of the large amount of environmental damage due to plastic waste and the large amount of plastic waste that we usually find in waterways which causes flooding everywhere. Environmental Awareness is one of the reasons for increasing public awareness to reduce the use of plastic waste and to start switching to sustainable packaging. In Indonesia, they have started to use sustainable packaging, but public awareness is still lacking and sometimes they still like to use plastic. The purpose of this research is to examine the impact of willingness to pay, environmental awareness, consumer behavior, and consumer attitudes toward purchasing decisions on sustainable packaging in Indonesia. Methods: A quantitative method was used as the research design method by conducting online questionnaires. The questionnaires were distributed online for those who have an intention to sustainable packaging in Indonesia. The total respondents in this research are 153. The data analysis design that is used in this research is Partial Least Square-based Structural Equation Modeling (PLS-SEM) using Smart-PLS software 4 starting from the measurement of the outer model, inner model, and hypothesis testing. Findings: This study has 4 hypotheses and the results show that willingness to pay, environmental awareness, consumer behavior, and consumer attitudes directly impact purchase decisions. Conclusion: Willingness to pay and consumer behavior significantly impact purchase decisions regarding sustainable packaging, whereas environmental awareness does not. Novelty/Originality of this Study: This comprehensive examination investigates how willingness to pay, environmental awareness, consumer behavior, and consumer attitudes specifically influence purchase decisions on sustainable packaging within the unique socio-economic and cultural context of Indonesia. By using Partial Least Squares-based Structural Equation Modeling (PLS-SEM), the study provides nuanced insights into the direct impacts of these variables, an area that is relatively unexplored in Indonesian market dynamics.